Art therapy to reduce burnout in oncology and palliative care doctors: a pilot study. Issue 1 (2nd January 2019) - Tjasink, Megan; Soosaipillai, Gehan
ABSTRACT: Doctors are frequently exposed to work-related stressors putting them at risk of burnout and affecting patient safety. This has long been recognised in oncology and palliative care staff members, with as many as 70% of young oncologists in Europe reporting burnout. Our objective was to use art therapy, which has been shown to combat the symptoms of burnout, on a cohort of trainee doctors in these high-risk specialities. In this pilot study, an art therapist ran three courses for oncology and palliative care trainee doctors, each comprised of six art therapy sessions. The Maslach Burnout Inventory – Human Services Survey (MBI-HSS) was completed pre- and post-intervention and a feedback questionnaire completed at the end of each course. Eighteen participants were recruited. MBI-HSS scores from 14 participants showed that the mean pre-intervention scores of the participants demonstrated burnout. Following the course there were statistically significant improvements in emotional exhaustion ( p =< 0.001) and personal achievement ( p  = 0.011) (removing one outlying participant's score from the latter). Feedback was overwhelmingly positive with most respondents finding the course 'very helpful'. The results of the pilot study demonstrated that six weeks of structured art therapy sessions resulted in positive change in our participants.